Effect of integrated yoga module on respiratory pressures and pulmonary functions in children - T., Jiwtode Manoj; R., Rathod Vyankatesh (International Journal of Research in Medical Sciences, 2017)
Background: Very often adults turn to practice of yoga when physical ailment is developed. Many research studies show effects of yoga in adults. Since childhood health forms a foundation for adult health, present work was planned to study the effects of yoga in children on pulmonary functions like forced expiratory volume in first second (FEV1), and peak expiratory flow rate (PEFR) and respiratory pressures like maximum expiratory pressure (MEP), maximum inspiratory pressure (MIP). Methods: 50 school children in the age group of 12 to 15 years were selected as cases. 50 age and gender matched students as control group. Students of study group were subjected to training of Integrated Yoga Module for 45 minutes a day for six days a week over a period of four months. Pulmonary function parameters were measured in both groups at the outset and at the end of study. Results were analyzed by Student’s paired ‘t’ test. Results: Yoga training produced statistically significant (p <0.05) increase in MEP (52.14 to 53.54 mmhg), MIP (- 61.04 to -61.98 mmhg), FEV1 (1.74 - 1.78 l) and PEFR (4.04 - 4.18 l/sec). In contrast, the increase in these parameters in the control group was statistically insignificant. Conclusions: From our study we conclude that yoga training for four months improves lung functions, strength of inspiratory and expiratory muscles in children. We also conclude if yoga is practiced since childhood, it can form a strong foundation for healthy adult life.